Pengaruh Penguasaan Teknologi Informasi Terhadap Kinerja Pegawai Badan Pusat Statistik Kabupaten Bone - A. Jumriah, Fajrianti Agus, Muh. Harisa P, Marniati Syam, Mustadir , (Pascasarjana STIE Amkop Makassar, 2024)
This study aims to determine the mastery of technology affects employee performance at the Bone Regency Statistics Agency office. This study uses a type of quantitative research to test hypotheses and determine the amount of influence between the independent variable and the dependent variable. The sample in this study used a saturated or census sampling method, saturated sampling is a sampling technique when all members of the population are used as samples. This is done because the population is relatively small, less than 40 people. The data analysis technique used in this research is simple linear regression The results of this study indicate that mastery of information technology has a positive and significant effect on the performance of employees of the Central Bureau of Statistics of Bone Regency. Keywords: mastery of information technology, employee performance